Astrophysical Bulletin - Balega, Yuri Yu.; SpringerLink (Online service) (Moscow : Pleiades Publishing : Imprint: Pleiades Publishing.)
Astrophysical Bulletin is an international peer reviewed journal that publishes the results of original research in various areas of modern astronomy and astrophysics, including observational and theoretical astrophysics, physics of the Sun, radio astronomy, stellar astronomy, extragalactic astronomy, cosmology, and astronomy methods and instrumentation.
Keywords: Astronomy; Astrophysics; Cosmology; Astronomy, Astrophysics and Cosmology